2012
DOI: 10.1111/j.1600-0501.2012.02505.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of different surface treatments on the bond strength of a gingiva‐colored indirect composite veneering material to three implant framework materials

Abstract: Application of priming agents containing specific phosphoric ester groups significantly enhances the bond strength of a gingiva-colored composite material to commercially pure titanium and zirconia frameworks. Combined use of a thione monomer with a phosphoric monomer enhances the bond strengths to airborne-particle abraded type IV gold alloy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
1
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 32 publications
2
22
1
2
Order By: Relevance
“…Failure of a layered structure usually occurs in the weakest material or the weakest interface of the unit. A study evaluating shear bond strength of a gingiva-colored indirect composite material to zirconia ceramics found that airborne-particle abrasion with alumina (alumina-blasting) followed by priming with specific functional monomers enhanced bond strength 21) . Alumina-blasting was reported to damage the surface integrity of high-strength ceramics [22][23][24] .…”
Section: Introductionmentioning
confidence: 99%
“…Failure of a layered structure usually occurs in the weakest material or the weakest interface of the unit. A study evaluating shear bond strength of a gingiva-colored indirect composite material to zirconia ceramics found that airborne-particle abrasion with alumina (alumina-blasting) followed by priming with specific functional monomers enhanced bond strength 21) . Alumina-blasting was reported to damage the surface integrity of high-strength ceramics [22][23][24] .…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, a gingiva-colored indirect composite material has been used to replace lost tissue architecture [17,18]. Koizuka et al [19] evaluated the bond strength of a gingiva-colored indirect composite to three different implant framework materials (gold alloy, titanium and zirconia ceramics) and the effect of surface pre-treatment with four priming agents. The results showed that bond strength for each framework material was influenced by the type of priming agent used.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the control group showed significantly lower bond strength than the treated five that the mechanical techniques yielded lower shear bond strength values than the chemical and mechanochemical bonding techniques (22). Airborne-particle abrasion creates surface roughness by cleaning the surface of metal oxides and increases the mechanical or chemical bond strength between metal substrates and composite material (23). In the present study, the airborne-particle abrasion significantly increased the bond strengths between the indirect composite and titanium framework.…”
Section: Discussionmentioning
confidence: 44%
“…The choice of a chemical bonding system for prosthodontic application may depend on factors such as expense, availability, time requirement, and shelf life of the perishable components (32). The functional monomer contained in priming agents can be classified into two categories; an acidic derivative carboxylic or phosphate monomer effective for base metals (23).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation